أثر برنامج التعليم بالفلسفة في تنمية التفكير الناقد والمشاركة الأكاديمية لدى طلبة ‏المرحلة الثانوية في المدارس السعودية بماليزيا - عرجا، محمد حسن عبدالجواد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aimed to identify the influence of the ‎Philosophical Inquiry Programme (PI), named as ‎Hikmah, on improving critical thinking skill and ‎academic engagement among secondary students at Arab ‎schools in Malaysia. The sample of the study consisted of ‎‎20 second year secondary students from the Saudi ‎Secondary School in Kuala Lumpur, Malaysia. To ‎achieve the objectives of the study, the action research ‎method was utilized, including the quasi-experimental ‎design with the application of a training program ‎‎(Philosophical Inquiry or Hikmah), in addition to a test ‎on critical thinking, a questionnaire on academic ‎achievement, observations, and interviews with students. ‎The study results showed that there were statistically ‎significant differences in the mean scores of critical ‎thinking skill among secondary students' before and after ‎the training program in favour of the post test. ‎Furthermore, the results revealed that there were ‎statistically significant differences in the mean scores of ‎secondary students' academic engagement due to the ‎training program. There was also a statistically ‎significant positive correlation or relationship between ‎critical thinking and academic engagement (p < 0.05) ‎after the application of the training program. These ‎results were triangulated with the researcher's ‎observations and the analysis of students' interviews, ‎which also showed the effectiveness of the training ‎program in enhancing the critical thinking skill and ‎academic engagement among second year secondary ‎students. ‎